2019
DOI: 10.1007/s43188-019-00009-1
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen-week inhalation toxicity study of 1-methylnaphthalene in F344 rats

Abstract: 1-Methylnaphthalene is generally utilized in solvents, as an intermediate in organic synthesis, a dye carrier, in resins, and others. There are some toxicological studies of 1-methylnaphthalene; however, inhalation toxicity studies are rare. Each of 10 male and female F344 rats was exposed to vapors of 1-methylnaphthalene for 13 weeks (6 h a day, 5 days per week) at concentrations of 0, 0.5, 4, and 30 ppm in a whole-body inhalation chamber system. The exposure concentrations were 0.52 ± 0.05, 4.08 ± 0.25, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Some of these chemicals, such as phthalates, have been linked to multiple chronic diseases, including reproductive disorders, diabetes, and thyroid function abnormality in epidemiological studies. Dibutyl phthalate has been recognized as a class 1B reproductive toxicant in the REACH authorization list, , and 1-methylnaphthalene has been reported as a neurotoxicant and lung carcinogen . Naphthalene and benzophenone classes are potential carcinogens due to radical formation after being transformed in humans …”
Section: Resultsmentioning
confidence: 99%
“…Some of these chemicals, such as phthalates, have been linked to multiple chronic diseases, including reproductive disorders, diabetes, and thyroid function abnormality in epidemiological studies. Dibutyl phthalate has been recognized as a class 1B reproductive toxicant in the REACH authorization list, , and 1-methylnaphthalene has been reported as a neurotoxicant and lung carcinogen . Naphthalene and benzophenone classes are potential carcinogens due to radical formation after being transformed in humans …”
Section: Resultsmentioning
confidence: 99%
“…Similar activities of transaminases were noted after 4-week exposure to 2-methylnaphthalene (1-MN isomer) at a dose of 50 mg/m 3 and after 13 weeks (6 h daily, 5 days/week) exposure to 1-MN at a dose of 30 ppm (approx. 174 mg/m 3 ) in rats of both sexes [ 32 , 33 ]. Based on the results of histopathological examinations, it was found that 1-MN mainly affected the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the no observed adverse effect level (NOAEL) is 4 ppm (approx. 23 mg/m 3 ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Murata et al [23] reported no lung toxicity in mice in a 13-week repeated dose toxicity study. However, Kim et al [24] reported that in the rats exposed by inhalation to 1-MN, some toxic effects were observed in the upper respiratory system and the no-observed-adverse-effect level was suggested to be 4 ppm on the basis of histopathological findings. In addition, 1-MN showed lung carcinogenicity in the mice fed a diet containing 0.075% or 0.15% 1-MN [23].…”
Section: Animal Groups and The Collection Of Biological Materialsmentioning
confidence: 99%